Diplomatic Protection: the Interpretation of International Legal Clauses of the Exhaustion of Local Remedies (Summary) - P. N. Biriukov (Московский журнал международного права, 2016)
The article deals with the principle of mutual recognition of foreign judgments in criminal matters. Author examines the issues arising from the implementation of Community instruments. The Spanish procedure of the implementation of the rules of EU Law is also investigated. The questions of execution and transmission of European orders in Spain, the procedure of interactionof the Spanish courts with competent authorities of foreign states, as well as the grounds for refusal by Spanish national law are considered.